Diagnostic Accuracy of Doppler Ultrasound in Detecting Parotid Tumors - Ihsan, Qurrat-ul-Ain; Khan, Kamran Ali (Biological and Clinical Sciences Research Journal, 2025)
Parotid tumors constitute the majority of salivary gland neoplasms and exhibit a wide histopathological spectrum, from benign pleomorphic adenomas to malignant mucoepidermoid carcinomas. Accurate preoperative diagnosis is critical for guiding management; however, limited access to advanced imaging techniques like CT and MRI in resource-constrained environments presents a challenge. Doppler ultrasound provides a non-invasive, cost-effective alternative for initial tumor evaluation. Objective: To assess the diagnostic accuracy of Doppler ultrasound in detecting parotid tumors, using histopathology as the gold standard. Methods: A prospective, cross-sectional study was conducted at the Burn Center, Hayatabad Medical Complex, Peshawar, from January 1 to June 30, 2024. A total of 124 patients presenting with clinically or radiologically suspected parotid tumors were enrolled. All patients underwent Doppler ultrasound using a high-resolution Mindray® system, with evaluation of parameters including lesion shape, margins, echogenicity, vascularity, resistive index (RI), and peak systolic velocity (PSV). Final diagnoses were established through histopathological examination. The diagnostic performance of Doppler ultrasound was assessed using 2×2 contingency tables to calculate sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy. Results: The mean age of participants was 42 ± 15.2 years, with a mean disease duration of 7.0 ± 3.5 months. Doppler ultrasound identified parotid tumors in 79 patients (63.7%), while histopathology confirmed 80 cases (64.5%). The sensitivity of Doppler ultrasound was 86.3%, specificity 77.3%, PPV 87.3%, NPV 75.6%, and diagnostic accuracy 83.1%. Conclusion: Doppler ultrasound demonstrates high diagnostic accuracy and serves as a valuable, non-invasive imaging modality for evaluating parotid tumors. It is especially beneficial in low-resource settings where access to advanced imaging is limited, supporting its role in early diagnosis and clinical decision-making.